Can vitamins and/or supplements provide hope against coronavirus? - Sarah M Michienzi (Drugs in Context, 2020)
Severe acute respiratory syndrome coronavirus-2 (SARS-COV-2) quickly became a global pandemic and has been responsible, so far, for infecting 5.8 million and claiming the lives of more than 350,000. While certain medications initially garnered attention as potential treatment options, further studies failed to demonstrate great promise but did demonstrate the need to reduce the cytokine storm experienced by patients with this potentially life-threatening virus. Unfortunately, there is no cure on the horizon, but members of the medical community are beginning to evaluate the potential role of vitamins and supplements as potential treatment options or addition to other treatments. The goal of this narrative review is to evaluate current and ongoing clinical trials of vitamins and supplements, alone or in combination with each other or other therapies, for the treatment of coronavirus disease-2019 (COVID-19).